A case report on retrieval of retained guidewire- a rare complication after central venous catheterization - Rajyaguru, Ajay M.; Chaudhary, Hiral D.; Baraiya, Yogesh L.; Hirapara , Harsh (International Journal of Research in Medical Sciences, 2023)
Central venous catheterization (CVC) is a routine technique which is widely used in fluid resuscitation, parenteral nutrition, haemodialysis and continuous invasive hemodynamic monitoring. CVC via the Seldinger technique is a minimally invasive procedure which is increasingly and widely performed. Popularity of the Seldinger technique of vascular cannulation has resulted in widespread use of spring guide wires. Though employed to make vascular cannulation easier and safer, guide wires are not without potential hazard. While the complication rate of inserting CVC catheters is approximately 11.8%, the intravascular loss of the guide wire during CVC placement is a rare but serious complication which is completely avoidable by appropriate care.